Spatial-Temporal Study of Stunting Risk in East Java 2021 - 2023 - Sofiyulloh, Sofiyulloh; Rahmaniati, Martya; Nugraha, Fajar (Universitas Nahdlatul Ulama Surabaya, 2025)
Stunting remains a significant global health issue affecting children, and Indonesia is still one of the countries with a high prevalence of stunting. Over the past three years, the prevalence of stunting in Indonesia was reached 24.4% in 2021, 21.6% in 2022, and 21.5% in 2023. East Java is one of the provinces still experiencing high stunting rates, although the figures are slightly below the national average. From 2021 to 2023, a decrease occurred, though not significantly. Several factors such as age at marriage and low birth weight are associated with the risk of stunting in East Java. This study employs a spatial-temporal approach through the visualization of stunting risk mapping using geographic information systems (GIS). Secondary aggregate data were obtained from the Indonesian Ministry of Health, BPS East Java, and digital maps sources. The h three-year autocorrelation analysis showed greater changes in the Moran's I value from 2021-2023, indicating changes in special pattern. In mapping the risk of stunting, there is a change in distribution of t high and low risk areas, although some areas remained in the same category. The results from the analysis and visualization in this study are expected to serve as valuable input for stakeholders to overcome stunting in East Java. Keywords: stunting, East Java, spatial, GIS, autocorrelation